Stasiun Pengisian Energi Baterai Ramah Lingkungan Berbasis Panel Surya - Ananda, Aprisal Surya; Hayati, Lilis Nur Hayati; As’ad, Ihwana (Prahasta Publisher, 2022)
The used of electrical power on gadgets is classified as minimal. However, if it is multiplied by the number of users, the electrical energy that required is not small. In the Sea Village, Latambaga, Kolaka, the courier services have sprung up and usually gathers to rest and charged their gadget batteries. However, couriers often charged their gadget batteries at restaurants or coffee shops, it could be detrimental to the restaurants or coffee shops owner because their electricity costs will increase. According to these problems, we need a device that is able to store the alternative energy, namely an Environmentally Friendly Battery Energy Charging Station. This research is based on solar panels, with the used of adequate battery capacity and an inverter as a DC-AC current converter so that it can be used to charge the couriers gadgets, the Telegram API bot as an IoT application for notification of device and battery power conditions to the admin device. This system is expected to help the couriers which operate in the villages of Sea, Latambaga, Kolaka in meeting the needs of environmentally friendly and inexpensive electrical energy.